2009
DOI: 10.1007/s00030-009-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of Positive Solutions for a Nonlinear Elliptic System

Abstract: Abstract. In this paper we study the uniqueness of nontrivial positive solutions for the following second order nonlinear elliptic system:We prove that for sufficiently small β > 0, the above system has a unique nontrivial positive solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…In fact, this conjecture was proved by Wei and Yao in [12] with the assumption i) β > max{ν 1 , ν 2 } or ii) β > 0 sufficiently small, see also Ikoma [6]. Employing the arguments used in [13], Nguyen, Tian, Deconinck and Sheils in [10] showed that the ground state is concerned with the best constant for the vector valued Gagliardo-Nirenberg inequality which in our case is…”
Section: Introductionmentioning
confidence: 63%
“…In fact, this conjecture was proved by Wei and Yao in [12] with the assumption i) β > max{ν 1 , ν 2 } or ii) β > 0 sufficiently small, see also Ikoma [6]. Employing the arguments used in [13], Nguyen, Tian, Deconinck and Sheils in [10] showed that the ground state is concerned with the best constant for the vector valued Gagliardo-Nirenberg inequality which in our case is…”
Section: Introductionmentioning
confidence: 63%
“…There are many works on the existence of non-trivial positive solutions of (1.5)- (1.8). See [2][3][4][5]11,12,[18][19][20]24,26,30,33,34]. Sign and size of β are important in the study of (1.5)-(1.8) and various situations are studied in the above papers.…”
Section: Introductionmentioning
confidence: 98%
“…Even in this case, it is not easy to get an explicit expression for E(y). To make matters worse, the uniqueness of a vector solution is known only for very restricted cases, typically in case W 1 (y) = W 2 (y) (refer to [20,36]). To overcome the difficulty in the characterization of a concentration point and the restricted knowledge on the uniqueness of a vector solution of a limiting problem in the construction for one bump vector solutions of (3), we approach the problem (3) with a new variational view point regarding (4) as a perturbation of ∇ L = 0 in a neighborhood of a set of approximate solutions in R N × (H 1 ) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…β,μ 1 ,μ 2 λ 1 ,λ 2 (γ (s, t)) ≤ max max (s,t)∈[1,R] 2 J β,μ 1 ,μ 2 λ 1 ,λ 2 (γ (s, t)), L λ 1 ,μ 1 , L λ 1 ,μ 1 ≤ max max (s,t)∈[0,R] 2 J β,μ 1 ,μ 2 λ 1 ,λ 2 (γ (s, t)), L λ 1 ,μ 1 , L λ 1 ,μ 1 = max (s,t)∈[0,R] 2 J β,μ 1 ,μ 2 λ 1 ,λ 2 (γ (s, t)) (20). …”
mentioning
confidence: 99%